2011
DOI: 10.1186/1477-7517-8-23
|View full text |Cite
|
Sign up to set email alerts
|

Patient and clinician's ratings of improvement in methadone-maintained patients: Differing perspectives?

Abstract: BackgroundIn the last few years there seems to be an emerging interest for including the patients' perspective in assessing methadone maintenance treatment (MMT), with treatment satisfaction surveys being the most commonly-used method of incorporating this point of view. The present study considers the perspective of patients on MMT when assessing the outcomes of this treatment, acknowledging the validity of this approach as an indicator. The primary aim of this study is to evaluate the concordance between imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 35 publications
0
22
0
2
Order By: Relevance
“…Attention needs to be paid to clients' voices throughout the treatment process and they should be involved in all decisions regarding substitute dosage and goal-setting. Research has demonstrated a clear gap between clients' and professionals' perceptions of the effectiveness of substitution treatment (Trujols et al, 2011). Consequently, goal setting should be based on a dialogical process to ensure that individual's goals and objectives correspond with the expectations and objectives of professional workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention needs to be paid to clients' voices throughout the treatment process and they should be involved in all decisions regarding substitute dosage and goal-setting. Research has demonstrated a clear gap between clients' and professionals' perceptions of the effectiveness of substitution treatment (Trujols et al, 2011). Consequently, goal setting should be based on a dialogical process to ensure that individual's goals and objectives correspond with the expectations and objectives of professional workers.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, goal setting should be based on a dialogical process to ensure that individual's goals and objectives correspond with the expectations and objectives of professional workers. Alternatively, the incorporation and monitoring of patient-reported outcomes such as quality of life and treatment satisfaction may contribute to more clientoriented services, based on individuals' needs and expectations (De Maeyer et al, 2011b;Trujols et al, 2011). Also, the provision of holistic, comprehensive services encompassing various life domains including psychosocial support is necessary to further improve the quality of OST and to promote opiate users' recovery and social inclusion (De Maeyer et al, 2011a;Vander Laenen, 2013;WHO, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Most treatment studies focused on putative objective parameters, while the subjective outcomes of MAT have received less attention. However, there is an increasing recognition that these constitute essential measures of MAT quality (Tiffany et al, 2012;Trujols et al, 2011;Uchtenhagen, 2015). Few studies have investigated subjective views of MAT episodes (Montagne, 2002;Stancliff, 2002), and, if so, mostly addressed patient satisfaction (Kelly et al, 2010;Marchand et al, 2011;Trujols et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These mostly concentrated on metaaspects, such as the provision of MAT and harm reduction (Deren et al, 2011;Forman et al, 2001;Notley et al, 2014), barriers to care (Schulte et al, 2013), the diversion and misuse of the substitute (Larance et al, 2011), reasons for dropout and treatment retention (Gutwinski et al, 2014) or combinations of the above (Besson et al, 2014). To our knowledge, Trujols et al (2011) conducted the only study investigating both provider and patient views of single MAT episodes (Trujols et al, 2011). Using patient and clinician versions of the Global Impression of Improvement Scale in a sample of 110 MAT patients, they demonstrated that patients and providers often have discordant perceptions of improvement in treatment (Trujols et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation